Anti‐apoptosis Function of PBCA Nanoparticles Containing Caspase‐3 siRNA for Neuronal Protection. Issue 4 (1st March 2018) - Zhang, Xiwei; Zhang, Enqi; Grigartzik, Lisa; Henrich‐Noack, Petra; Hintz, Werner; Sabel, Bernhard A.
Abstract: Poly(butylcyanoacrylate) nanoparticles (PBCA NPs) have the ability to cross the blood‐brain barrier and deliver pharmaceuticals into the brain. Caspase‐3 (Casp3)‐siRNA loaded NPs were designed to investigate the possibility of anti‐apoptotic treatment. NPs were produced in a miniemulsion and optimized according to size and zeta potential. Casp3‐PBCA NP induced anti‐apoptotic effect was observed by an MTT test and siRNA caused knock‐down effect was identified by using a western blot assay. Further, rhodamine‐123 labeled PBCA NPs were visualized by in vivo imaging to investigate the blood‐brain barrier passage in a rodent experiment. Abstract : Poly(butylcyanoacrylate) nanoparticles are able to cross the blood‐brain barrier and deliver drugs into the brain. Anti‐casp3‐siRNA loaded nanoparticles were designed to investigate the anti‐apoptotic effect in C6 glioma cells. Modified nanoparticles were produced in a W/O miniemulsion polymerization process and optimized according to size, polydispersity, and zeta potential.